Business Competition Law Enforcement by the Business Competition Supervisory Commission in Territorial Division Agreements - Rommy Hardyansah; Didit Darmawan; Fayola Issalillah; Rafadi Khan Khayru Khayru; Rahayu Mardikaningsih (Civiliza Publishing, 2025)
he Business Competition Supervisory Commission (KPPU) serves as the primary institution responsible for enforcing competition law in Indonesia, established under Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This study aims to analyze the role of KPPU in exercising its law enforcement function, particularly in handling territorial division agreements among business actors. The research employs a normative juridical approach with analytical descriptive specifications, examining positive legal provisions governing business competition and KPPU's authority under Law Number 5 of 1999, KPPU Regulation Number 1 of 2014, and KPPU Regulation Number 2 of 2023. The findings reveal that KPPU possesses comprehensive authority encompassing investigative, examining, prosecutorial, adjudicative, and consultative functions. In enforcing Article 9 concerning territorial division agreements, KPPU applies the rule of reason approach, requiring concrete evidence and in-depth evaluation of the agreement's impact on competition. Sanctions for violations include administrative measures under Article 47 and criminal penalties under Article 48, with fines ranging from IDR 25 billion to IDR 100 billion or imprisonment substitution for up to six months. KPPU has also introduced an integrity pact mechanism for behavioral change under KPPU Regulation Number 2 of 2023, allowing business actors to voluntarily commit to canceling prohibited agreements and ceasing violative activities. Despite KPPU's extensive enforcement authority, execution of final and binding decisions remains under judicial purview as stipulated in Article 46 paragraph (2), requiring coordination between KPPU and district courts. The study concludes that strengthening institutional capacity, enhancing regulatory clarity in rule of reason application, expanding preventive supervision, and improving coordination with the judiciary are essential for optimizing KPPU's law enforcement function in maintaining fair business competition and protecting consumer welfare in Indonesia.